Saving the city : philosopher-kings and other classical paradigms - Schofield, Malcolm (Issues in ancient philosophy., 1999)
Saving the City provides a detailed analysis of the attempts of ancient writers and thinkers, from Homer to Cicero, to construct and recommend political ideals of statesmanship and ruling, of the political community and of how it should be founded in justice. Malcolm Schofield debates to what extent the Greeks and Romans deal with the same issues as modern political thinkers.